设二次型 $f\left(x_1, x_2, x_3\right)=x_1^2-2 x_2^2+a x_3^2+2 x_1 x_2-4 x_1 x_3+2 x_2 x_3$, 经可逆线性变换 $\boldsymbol{x}=\boldsymbol{P y}$ 化为二次型 $g\left(y_1, y_2, y_3\right)=y_1^2+y_2^2-2 y_3^2+2 y_1 y_2$, 则 $a=$
【答案】 1

【解析】 【解析】记二次型 $f, g$ 的矩阵分别为 $\boldsymbol{A}, \boldsymbol{B}$, 依题意, $\boldsymbol{A}=\left[\begin{array}{ccc}1 & 1 & -2 \\ 1 & -2 & 1 \\ -2 & 1 & a\end{array}\right]$, $\boldsymbol{B}=\left(\begin{array}{ccc}1 & 1 & 0 \\ 1 & 1 & 0 \\ 0 & 0 & -2\end{array}\right), \boldsymbol{A} \simeq \boldsymbol{B}$, 故 $r(\boldsymbol{A})=r(\boldsymbol{B})$, 由 $\boldsymbol{B}=\left(\begin{array}{ccc}1 & 1 & 0 \\ 1 & 1 & 0 \\ 0 & 0 & -2\end{array}\right) \rightarrow\left(\begin{array}{ccc}1 & 1 & 0 \\ 0 & 0 & 1 \\ 0 & 0 & 0\end{array}\right)$, 得 $r(\boldsymbol{A})=r(\boldsymbol{B})=2$, 于是 $|\boldsymbol{A}|=\left|\begin{array}{ccc}1 & 1 & -2 \\ 1 & -2 & 1 \\ -2 & 1 & a\end{array}\right|=3(1-a)=0$, 得 $a=1$.
系统推荐